PEMBUATAN VIRGIN COCONUT OIL (VCO) DENGAN METODE PENGASAMAN SEBAGAI KRIM TABIR SURYA BERBAHAN AKTIF TiO2 - Agung Giri Samudra; Nurfijrin Ramadhani; Fathnur Sani K; Ulfa Febriyani (jurnal ilmiah manuntung sekolah tinggi ilmu kesehatan samarinda, 2020)
Palm trees is one plantation commodities important in development sub the plantation sector, among others to meet the needs of domestic, and as a commodity export foreign exchange producing countries. Cream sunscreen is made with an emulsion phase (VCO, lanolin, stearic acid and cetyl alcohol) and aqueous phase (triethanolamine, glycerin, aquadest). TiO2 was added with various concentrations of F0 (0%), F1 (5%), F2 (10%), and F3 (15%). The research vco oil colorless and odorless typical fresh coconut. Produce the centrifugation does not happen the separation between the oil and the water pH value the range of 6.87-7.63; viscosity and range of cp 12400-21600; SPF value at F0 (0.189); F1 (2.857); F2 (4.252); F3 (6.154). Of the value of the two of them have met the standards according to the SPF concentration F2 and F3.